PROGRAMMING FUNDAMENTALS TEACHING TO THE STUDENTS OF PHYSICO-MATHEMATICAL PROFILE - Vdovychyn Tatiana; Lazurchak Liubov (Kherson State University, 2017)
The article provides methodical recommendations on studying of the discipline "Informatics" for the specialists preparation of the first (Bachelor) level of higher education of the field of knowledge 01 "Education" of the specialty 014.04 "Secondary education (mathematics)", 014.08 "Secondary education (physics)". This discipline plays a particularly important role in the higher education establishments physical and mathematical field specialists training, since it combines both the fundamental concepts and principles of various mathematical and informatics disciplines, as well as applied models and algorithms for their application. The methodological aspects of the discipline "Informatics" study include the pedagogical feasibility of the forms, methods and means of training for students who are qualified as a teacher of mathematics and a physics teacher respectively. The discipline program includes issues on informatics theoretical foundations, applied software, and the basics of programming. Students are encouraged to consider the basics of programming in the C ++ environment. Basic C ++ language designs have a convenient, professional programming toolkit. Integrated C ++ environment is characterized by speed, convenience in debugging and compiling of the program. Therefore, the article focuses on the practical skills formation in the C ++ environment for the students of the physical and mathematical profile and highlights the methodological aspects of the C ++ programming language use in the course of the discipline "Informatics" teaching. The formation of practical skills takes place during the performance of laboratory works, namely: the original problem setting, the construction of an algorithm for its solution, analysis of the received results.